Protein Profile Analysis of Tungro and Dwarf Virus-Infected Rice Plants using SDS-PAGE - Saipul Abbas (Jurnal Biologi Tropis, 2023)
Viruses in rice plants are one of the causes of decreased harvest yields and rice farming productivity. This study aims to analyze the protein profile of viruses in rice plants infected with tungro and dwarf viruses using the SDS-PAGE method. The study includes six plant samples, including tungro-infected plants from Pinrang and Sidrap districts, as well as dwarf virus-infected plants from Sidrap and Wajo districts. Two healthy plant samples were used as a comparison. The SDS-PAGE technique was employed for the separation and analysis of proteins. The protein profile results in tungro-infected plants showed a protein band pattern between 31-116 kDa. Meanwhile, in dwarf virus-infected plants, a protein band pattern between 31-205 kDa was detected. These results indicate variations in protein expression between viruses and significant differences in protein profiles between tungro and dwarf virus-infected plants compared to healthy plants. Therefore, it is expected that this information can aid in designing more effective strategies for controlling virus infections in rice plants.